Pengaruh Volume Media Dalam Polybag Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis Jacq.) - Khairil Fikri; Murniati '; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aimed to determine the response of the growth of oil palm seedlings with various media volume in the main nursery. The research was conducted in the greenhouse of the Faculty of Agriculture University of Riau, Pekanbaru. The study lasted for 7 months starting in January 2012 until July 2012. The research was carried out experimentally by using completely randomized design consisting of three (3) treatment with 6 (six) replicates that contained 18 experimental units. Each unit consists of 2 seeds. Total whole plant 36 seedlings were planted in 36 polybags. Treatment is the media volume consists of 3 levels ie: V1 = 8 liter/polybag, V2 = 7 liter/polybag, and V3 = 6 liter/polybag. Parameters measured were seedling height, number of leaf midrib, stump diameter, crown root ratio and dry weight of seedlings. The results showed that significantly affects the media volume increase in plant height parameters. But non-significantly to the amount of leaf midrib, plant bulbs diameter, crown ratio and dry weight of seedling roots. Keywords: media volume, oil palm seedlings.